2019
DOI: 10.3390/medicina55070341
|View full text |Cite
|
Sign up to set email alerts
|

Non-Skeletal Activities of Vitamin D: From Physiology to Brain Pathology

Abstract: Vitamin D is a secosteroid hormone regulating the expression of almost 900 genes, and it is involved in the regulation of calcium and phosphate metabolism, immune response, and brain development. Low blood vitamin D levels have been reported in patients affected by various diseases. Despite a large amount of literature data, there is uncertainty surrounding the role of vitamin D as a serum biomarker in Alzheimer’s disease (AD) and Parkinson’s disease (PD). Indeed, the lack of internationally recognized 25(OH)D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 86 publications
(95 reference statements)
1
69
0
2
Order By: Relevance
“…Hypovitaminosis D appears to play an important role in a number of extraskeletal diseases such as several autoimmune diseases [8,9] or Alzheimer's and Parkinson's disease [10]. Vitamin D plays a key role in various physiological processes such as the regulation of brain development and activities in adulthood [11]. The serum value is considered the most significant indicator for vitamin D storage.…”
Section: Introductionmentioning
confidence: 99%
“…Hypovitaminosis D appears to play an important role in a number of extraskeletal diseases such as several autoimmune diseases [8,9] or Alzheimer's and Parkinson's disease [10]. Vitamin D plays a key role in various physiological processes such as the regulation of brain development and activities in adulthood [11]. The serum value is considered the most significant indicator for vitamin D storage.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D is involved in calcium and phosphate metabolism, the immune response and regulation of brain development. Vitamin D was a good candidate serum biomarker for PD and Alzheimer's disease [37] ( Figure 3A). The analysis of cell composition showed that the differential proteins were secretory proteins, mostly from the extracellular matrix and membrane ( Figure 3B).…”
Section: Functional Enrichment Analysis Of Differential Proteinsmentioning
confidence: 99%
“…In the scientific literature, it is known the classical role of vitamin D in regulating calcium and phosphorus homeostasis [1]. Vitamin D increases intestinal calcium uptake and phosphorus reabsorption at the tubular level, stimulates mineralization of osteoid tissue, promotes calcium and phosphorus deposition in the form of hydroxyapatite crystals [2].…”
Section: Introductionmentioning
confidence: 99%